Assessment of Knowledge, Attitude, and Practice of Skilled Assistance Seeking Maternal Healthcare Services and Associated Factors among Women in West Shoa Zone, Oromia Region, Ethiopia - Eden Girmaye; Kassa Mamo; Birhanu Ejara; Fikadu Wondimu; Maru Mossisa (Hindawi Limited, 2021)
Background. This study aimed to assess women's knowledge, attitude, and practice towards skilled assistance seeking maternal healthcare services in West Shoa Zone, Oromia Region, Ethiopia. Methods. Cross-sectional survey design was conducted from 1 February to 23 March 2018 in West Shoa Zone, Oromia, Ethiopia. A simple random sampling technique was used to select the participants. The data were collected using a pretested and structured questionnaire. Data were entered using EpiData version 3.1, and descriptive analysis and bivariate and multivariate logistic regression analyses were carried out using SPSS version 20 statistical software package. Results. The study revealed that the knowledge, attitude, and practice towards skilled maternal health services were found such that 473.3 (72.4%) of the study participants had good knowledge, 180.7 (27.6%) had poor knowledge, and 400 (61.3%) had positive attitude, 254 (38.84%) had negative attitude, 460.3 (70.4%) had good practice, and 193.7 (29.6%) had poor practice towards skilled maternal health services. Factors that had a significant association with antenatal care utilization were planned pregnancy (AOR = 8.2, 95% CI = 3.39-19.78-0.87) and access to transport (AOR = 3.1, 95% CI = 1.46-6.61). Attending ANC at least once (AOR = 3.1, 95% CI = 1.13-8.41), women's education (AOR = 3.0, 95% CI = 1.18-7.84), and unplanned pregnancy (AOR = 0.3, 95% CI = 0.21-0.75) were factors associated with skilled delivery service utilization. Attending ANC at least once (AOR = 2.1, 95% CI = 1.1-4.2), birth complications (AOR = 2.2, 95% CI = 1.35-3.66), unplanned pregnancies (AOR = 0.3, 95% CI = 0.22-0.68), and awareness about skilled obstetric care (AOR = 3.7, 95% CI = 1.68-12.79) were factors associated with postnatal care utilization. Conclusions. This study found that the knowledge, attitude, and practice of skilled maternal health services among the study participants are low, showing less than three-quarters of the total sample size. Therefore, this study implied that interventions are required to improve women's knowledge, attitude, and practice of skilled maternal health services in the study area. Furthermore, women's education is significantly associated with skilled delivery service utilization. Accordingly, this study recommends that improving equity among the marginalized population is needed to increase maternal health service coverage.